Risk management in HIV/AIDS: ethical and economic issues concerning the restriction of HAART access only to adherent patients - Chawana, Richard (My University, 2011)
South Africa, like many other developing nations, is faced with the challenge of mobilising resources to fight the HIV/AIDS pandemic. There is a huge budget gap between the ideal and actual funding provided to achieve universal access to highly active antiretroviral therapy (HAART), which leads to the inevitable rationing of HAART. Although healthcare spending has been increasing in South Africa, new demands are being placed on the HAART roll out programmes. This is particularly due to the emergence of HIV drug resistance (HIVDR). Because non-adherence to HAART is strongly linked to drug resistance, this is a major threat to any successful HAART programme. In the face of restricted resources, this research report looks at some of the ethical and economic implications of non-adherence to HAART. I suggest that there is merit in considering that HAART be restricted only to adherent patients.
MSc (Med), Bioethics and Health Law, Faculty of Health Sciences, University of the Witwatersrand
Keywords: HAART; ethics; adherent patients; access; HIV/AIDS